Dietary nutrient manipulation to improve the performance and tibia characteristics of broilers fed oak acorn (Quercus Brantii Lindl) - Houshmand,M (2015)
An experiment was conducted to evaluate the effects of dietary nutrients (protein, methionine, and choline) manipulation on the performance and tibia characteristics of broilers fed diets containing 15% oak acorn. A completely randomized design with five treatments and four replicates of 15 chicks each, was used. One group was fed a diet based on corn (without oak acorn) as control and other four groups were fed diets containing oak acorn with one of the following nutrient manipulation: without nutrient manipulation, high level of methionine (100% more than NRC), high level of CP (10% more than NRC), and addition of 0.2% choline. Starter and finisher diets were fed from one to 21 and 22 to 42 d of age, respectively. The results indicated that group fed diet without nutrient manipulation presented higher feed intake and worse feed conversion ratio (p<0.05) compared with the control group throughout the experiment. Elevated levels of methionine, protein, and choline had significant beneficial effects on feed conversion ratio during starter phase. Feeding oak acorn negatively influenced tibia bone characteristics (bone ash and strength) both at 21 and 42 d of age, whereas the supplementation with protein, methionine and choline prevented those negative effects. In conclusion, dietary inclusion of 15% oak acorn had negative effects on broiler performance and tibia characteristics. Detrimental effects of oak acorn, particularly on tibia bone, were reduced or prevented by increasing the dietary levels of choline, methionine, and protein.